Dissolved Organic Carbon Dynamics in Constructed and Natural Fens in Athabasca Oil Sands Development Region near Fort McMurray, Alberta - Khadka, Bhupesh (Graduate Studies, 2014)
Peatlands, mainly fens, are largely disturbed in order to recover bitumen below the surface in the Athabasca oil sands development region, Alberta. Mine closure plans require ecosystem reclamation: hence fen construction method is being investigated. In this study, dissolved organic carbon (DOC) dynamics in a constructed fen were compared with three other diverse natural fens in the region. The constructed fen had lower soil DOC concentration than all natural fens. Based on E2/E3, E4/E6 and SUVA254 of the DOC, the constructed fen had DOC with significantly greater humic content, aromatic nature and larger molecular size than the natural fens. A laboratory DOC production study revealed that these patterns are likely due to the limited DOC contribution from newly planted vegetation at the constructed fen resulting in DOC largely derived from humified peat. These preliminary results suggest that DOC dynamics in the constructed system could be useful for evaluating reclamation success through time.